(untitled) (Eurasian Journal of Philology Science and Education, 2020)
The relevance of the article lies in the fact that the study of euphemisms from a functional point of view is considered one of the most important problems of linguistics. The study reveals the stylistic possibilities, functional features and ways of using phraseological euphemisms in various spheres of social activity of human life, such as news, politics and business, and creates the basis for a deep understanding of the expressive resources of the English language. In addition, a comprehensive semantic and stylistic analysis of passages taken from the news on the crisis of Greece and the current state of the European Union. Given the versatility of news texts (political, economic, etc.) downloaded from the official websites of the BBC, VOA, CNN in English, we set the goal of our study. The purpose of the article is to study the functional aspects of phraseological euphemisms. The purpose of the study includes the following tasks: to explore the theoretical principles and various euphemisms and dyspremisms that exist in modern society; identify the main aspects, especially the functional aspects of euphemisms in various social spheres of human activity, including news, politics and business. The novelty of the study is that in English, the functional aspects of euphemisms are primarily studied in the linguistics of the text. The subject of this research is news material from bbcnews.com, where euphemisms are used in authentic English texts. The subject of this article is the study of phraseological euphemisms used in various social spheres of human activity, such as news, politics and business. Article methods include semantic and contextual analysis, as well as functional analysis of the problem. The materials used in the study include authentic materials downloaded from the official websites of the BBC, VOA, CNN in English, theoretical books and manuals of local and foreign scientists. It also includes modern dictionaries of English euphemisms.